2000
DOI: 10.1093/ije/29.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on the relation of cigarette smoking with cancer of the liver and stomach in an endemic region

Abstract: The highest incidence of stomach cancer worldwide and a relatively high incidence of liver cancer are found in the Japanese population. 1 There is considerable geographical variation in cancer mortality in Japan: e.g. the western region has a higher liver cancer mortality rate than the northern region. 2 Such differences in mortality might be explained by hepatitis virus infection in the case of liver cancer, [3][4][5][6][7][8] and by diet and Helicobacter pylori infection in the case of stomach cancer. 9 Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
1
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 41 publications
(43 reference statements)
5
57
1
1
Order By: Relevance
“…No role of tobacco smoking was found also in two small casecontrol studies carried out in Greece and Spain (Vall Mayans et al, 1990;Hadziyannis et al, 1995). Among some large cohort studies performed in East Asia, a few showed an increased risk of death from liver cancer among smokers compared to non-smokers (Goodman et al, 1995;Liaw and Chen, 1998;Liu et al, 1998;Mizoue et al, 2000), but those that took account of HBV and HCV infection and alcohol intake did not find the association (Mori et al, 2000;Evans et al, 2002;Sun et al, 2003).…”
Section: Tobacco Smokingmentioning
confidence: 96%
“…No role of tobacco smoking was found also in two small casecontrol studies carried out in Greece and Spain (Vall Mayans et al, 1990;Hadziyannis et al, 1995). Among some large cohort studies performed in East Asia, a few showed an increased risk of death from liver cancer among smokers compared to non-smokers (Goodman et al, 1995;Liaw and Chen, 1998;Liu et al, 1998;Mizoue et al, 2000), but those that took account of HBV and HCV infection and alcohol intake did not find the association (Mori et al, 2000;Evans et al, 2002;Sun et al, 2003).…”
Section: Tobacco Smokingmentioning
confidence: 96%
“…13 The followup has been described in detail elsewhere. 14,15 Briefly, the baseline survey was conducted from 1986 to 1989. We invited all inhabitants aged from 30 to 79 years living in A town, B village, and selected districts of C city and D town (15,417 subjects in total) to participate in a self-administrated questionnaire survey.…”
Section: Study Populationmentioning
confidence: 99%
“…Our cohort study was started in Fukuoka Prefecture in 1986 -89, and the follow-up method has been described elsewhere (Fujino et al, 2001;Mizoue et al, 2000;Utoguchi et al, 1997). The number of subjects who were invited to participate and fill in a self-administered questionnaire was 15 417.…”
Section: Study Populationmentioning
confidence: 99%